Worker Representatives - Julian Budde; Thomas Dohmen; Simon Jäger; Simon Trenkle (Institute of Labor Economics (IZA), 2024)
We study the descriptive and substantive representation of workers through worker representatives, focusing on the selection of German works council representatives and their impact on worker outcomes. Becoming a professional representative leads to substantial wage gains for the elected, concentrated among blue-collar workers. Representatives are positively selected in terms of pre-election earnings and person fixed effects. They are more likely to have undergone vocational training, show greater interest in politics, and lean left politically compared to the employees they represent; blue-collar workers are close to proportionally represented among works councilors. Drawing on a retirement-IV strategy and event-study designs around council elections, we find that blue-collar representatives reduce involuntary separations, consistent with blue-collar workers placing stronger emphasis on job security.
Keywords: J51; J53; P16; 330; representation; works-councils; unions; blue-collar worker